Added Value of Extragenital Sexually Transmitted Infection Testing in "IWantTheKit" Program Users - Yu, Tong; Melendez, Johan H; Armington, Gretchen S; Silver, Barbara; Gaydos, Charlotte A; Ruby, Kenneth; Olthoff, Glen; Greenbaum, Adena; Hamill, Matthew M; Manabe, Yukari C (Sexually transmitted diseases, 2023)
The 2021 Centers for Disease Control and Prevention sexually transmitted infection treatment guidelines recommend extragenital testing for gonorrhea and chlamydia in men who have sex with men and for women based on reported behaviors and exposures. The "IWantTheKit (IWTK)" program is a free online platform for specimen self-collection and mail-in for combined chlamydia/gonorrhea testing. We sought to assess the additional diagnostic value of extragenital testing compared with genital testing only for chlamydia/gonorrhea and determine factors associated with a positive extragenital test result among IWTK users. From August 2013 to January 2022, 7612 unique IWTK users returned swabs for testing; 3407 (45%) users requested both genital and extragenital tests and were included in this analysis. Descriptive statistics were summarized for demographic characteristics, reported behaviors, and genital and extragenital test results, and data were stratified by gender and age group. A logistic regression model was used to estimate associations between factors and extragenital sexually transmitted infection positivity. Chlamydia positivity rates were 4.7%, 2.4%, and 1.5% at genital, extragenital, and both sites, respectively; for gonorrhea, 0.4%, 1.1%, and 0.4% were positive at those sites, respectively. Among women, age 25 years and younger was significantly associated with extragenital chlamydia (odds ratio [OR], 4.0; P = 0.010). Being in high-risk quiz score group was associated with extragenital chlamydia (OR, 2.6; P = 0.005) and extragenital gonorrhea in men and women (OR, 8.5; P = 0.005). Extragenital testing detected additional chlamydia and gonorrhea cases in the IWTK user population that would have been missed by genital-only testing, especially for women younger than 25 years and people reported to be at high risk.